MODEL PENDEKATAN HUMANISTIK DALAM PENGELOLAAN KELAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM SDN PALUMBONSARI 1 - Umam, Choerul; Ferianto, Ferianto (Universitas Islam Negeri Sumatera Utara Medan, 2023)
This study aims to explain and analyze an effective classroom management model in the subject of Islamic Religious Education (PAI). Good and effective classroom management is the key to success in teaching PAI, as it creates a conducive environment for students to acquire understanding and develop religious values. This research utilizes a qualitative approach by analyzing literature, teaching guidelines, and classroom observations. The results of the study show that the applied humanistic approach model in SDN Palumbonsari 1 contributes positively to the teaching of Islamic Religious Education. Teachers use this approach to develop students' potential, reinforce their understanding of Islamic values, and promote inclusive and tolerant attitudes. Moreover, the implementation of the humanistic approach model also encourages active student participation in the learning process through group discussions, reflective activities, and real-life experiences. Therefore, this classroom management model can serve as a reference for PAI teachers in other schools to enhance the effectiveness of teaching PAI.